2018
DOI: 10.1002/ijgo.12431
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HPV persistence and cytology anomalies at follow‐up after treatment for cervical dysplasia

Abstract: Clinical factors, including age, smoking, treatment history, and status of surgical margins, could help to determine the risk of dysplasia recurrence and facilitate patient follow-up based on risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In multivariate analysis, the hrHPV persistence rates were not affected by the status of resection margin ( P =0.528), however a positive resection margin was associated with a 1.94-fold higher risk of hrHPV persistence ( P <0.05) in univariate analysis. As several previous studies have pointed out [ 13 , 20 , 28 , 29 ], a positive resection margin is the most significant risk factor for predicting hrHPV persistence and residual/recurrent CIN-2/3. However, a negative resection margin does not always indicate complete excision due to the possibility of multifocal lesions.…”
Section: Discussionmentioning
confidence: 91%
“…In multivariate analysis, the hrHPV persistence rates were not affected by the status of resection margin ( P =0.528), however a positive resection margin was associated with a 1.94-fold higher risk of hrHPV persistence ( P <0.05) in univariate analysis. As several previous studies have pointed out [ 13 , 20 , 28 , 29 ], a positive resection margin is the most significant risk factor for predicting hrHPV persistence and residual/recurrent CIN-2/3. However, a negative resection margin does not always indicate complete excision due to the possibility of multifocal lesions.…”
Section: Discussionmentioning
confidence: 91%
“…A US-based study among young women reported that smoking was protective against persistent HPV infection, but researchers were unsure whether it was because of a biological or a confounding effect 21 . In another UKbased study, no association between smoking and persistent HR-HPV infection was found, partly on account of the short 6-month follow-up 9 .…”
Section: Discussionmentioning
confidence: 89%
“…As a well-known risk factor for the progression of cervical lesions with HPV infection, smoking was supposed to promote a persistent infection. However, the association has never been clearly evaluated, and some previous studies have found negative 21 or null 9,[15][16][17][18]22 associations between current smoking and HPV persistent infection. The inconsistency of these studies may be due to different definitions of HPV persistence or clearance, sample sizes, followup intervals and durations and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common types of HPV are viral types 16 and 18 [1]. Persistent high-risk (HR) HPV infections are significantly related to the progression of CIN2-3 and are thought to progress to cervical cancer [2]. Conservative therapy with a loop electrosurgical excision procedure (LEEP) has been performed to diagnose or treat CIN2-3 [3].…”
Section: Introductionmentioning
confidence: 99%